SPIROWPLAST (Spirulina and arrowroot bioplastic): A combination of Spirulina and arrowroot to enhance the tensile strength and durability of bioplastic - Amira Liontina Ichlasia; Zameera Adelia; Roosita Damayanti; Putri Dyah Astari; Wahyu Disky Pratama; Adian Khoironi (Journal of Emerging Science and Engineering, 2026)
Plastic waste that is resistant to natural degradation remains a critical environmental challenge. One promising strategy to address this issue is the development of bioplastics derived from renewable, biodegradable resources. This study investigates the potential of combining Spirulina platensis and arrowroot (Maranta arundinacea) flour to produce bioplastics with improved mechanical, chemical, and biodegradation performance. An experimental approach was employed using four formulations: bioplastics derived solely from S. platensis, solely from arrowroot flour, a composite of S. platensis and arrowroot flour, and a commercial bioplastic (ecoplast) as a positive control. Comprehensive characterization was conducted using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), tensile strength, thickness measurement, and biodegradation tests in accordance with ASTM standards. The results demonstrate that the combined Spirulina–arrowroot formulation exhibits more balanced and superior properties compared to single-component bioplastics. The composite bioplastic achieved a tensile strength of 4.267 MPa and an elongation at break of 105.5%, approaching the performance of commercial bioplastic. FTIR analysis confirmed the presence of key functional groups, including hydroxyl (–OH), carboxyl (–COOH), ester (C–O), and aromatic structures, indicating effective polymer network formation. SEM observations revealed a smoother and denser surface morphology, while XRD analysis indicated a semi-crystalline structure with a crystallinity of 49.6%. All bioplastic samples fully decomposed in composted soil within three days, highlighting their excellent biodegradability. Overall, the combination of Spirulina platensis and arrowroot flour effectively compensates for the limitations of each individual material, yielding a strong, flexible, and rapidly degradable bioplastic. These findings suggest a viable and environmentally friendly alternative to conventional plastics and provide a foundation for the future development of large-scale bioplastic products with properties comparable to commercial materials.